2014
DOI: 10.1038/cr.2014.3
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian WTAP is a regulatory subunit of the RNA N6-methyladenosine methyltransferase

Abstract: The methyltransferase like 3 (METTL3)-containing methyltransferase complex catalyzes the N6-methyladenosine (m6A) formation, a novel epitranscriptomic marker; however, the nature of this complex remains largely unknown. Here we report two new components of the human m6A methyltransferase complex, Wilms' tumor 1-associating protein (WTAP) and methyltransferase like 14 (METTL14). WTAP interacts with METTL3 and METTL14, and is required for their localization into nuclear speckles enriched with pre-mRNA processing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

49
1,688
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 1,853 publications
(1,800 citation statements)
references
References 58 publications
49
1,688
1
1
Order By: Relevance
“…2b). In addition to the known MTA‐FIP37 interaction (Zhong et al ., 2008), we observed heterodimerization of the Arabidopsis MTA and MTB, consistent with the reported interaction between their mammalian orthologues METTL3 and METTL14 (Liu et al ., 2014; Ping et al ., 2014; Wang et al ., 2014b). We also found that MTB but not MTA formed homodimers in Y2H.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…2b). In addition to the known MTA‐FIP37 interaction (Zhong et al ., 2008), we observed heterodimerization of the Arabidopsis MTA and MTB, consistent with the reported interaction between their mammalian orthologues METTL3 and METTL14 (Liu et al ., 2014; Ping et al ., 2014; Wang et al ., 2014b). We also found that MTB but not MTA formed homodimers in Y2H.…”
Section: Resultsmentioning
confidence: 99%
“…Orthologues of MTA and MTB interact with each other and with orthologues of FIP37 in S. cerevisiae (Agarwala et al ., 2012) and human cells (Liu et al ., 2014; Ping et al ., 2014; Schwartz et al ., 2014; Wang et al ., 2014b). In S. cerevisiae , writing of m 6 A requires orthologues of MTA (IME4), FIP37 (MUM2) and the yeast‐specific SLZ1 (Agarwala et al ., 2012).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations